Boundaries, crosscaps and simple currents - Fuchs, Jürgen; Walcher, Johannes (Physics letters, 2000)
Universal formulas for the boundary and crosscap coefficients are presented, which are valid for all symmetric simple current modifications of the charge conjugation invariant of any rational conformal field theory.
Gesehen am 21.02.2020